COVID-19 pandemic experiences of students from BAME and White ethnic groups pursuing higher education in the UK: A qualitative comparative exploration - Hitch, Geeta; Zaman, Shahaduz (Frontiers in Psychiatry, 2023)
Background The new severe acute respiratory syndrome coronavirus 2, SARS-Cov2, more commonly known as COVID-19 continues to be an ongoing cause of one of the most disruptive pandemics worldwide. UK universities comprise students who come from different backgrounds and cultures and the majority returned home or lived alone during the lockdown. This qualitative study aimed to compare the experiences of students from Black, Asian, and Minority Ethnic (BAME) backgrounds and White British students. Materials and methods An in-depth interview was conducted with each of 35 students—18 from BAME and 17 from White backgrounds—in their homes on Zoom or Microsoft between November 2020 and May 2021. Interview transcripts were checked for accuracy and were analysed using N-Vivo coding software for themes. The pre-pandemic and pandemic experiences of students were collected in the form of a data, including perceptions of the COVID-19 virus, the physical environment in which students lived, and the effect on their general wellbeing, social interactions, online learning, teaching, and assessment. Results Mental health issues were more prevalent among female students compared to males and this was more evident amongst BAME females who had returned to living at home, possibly due to lack of personal space. There was a reduction in personal hygiene in White females. There was an increase in the use of social media, particularly by BAME females. Students mostly disliked online learning and exams. Concerns were also raised about how universities communicated important information to the students. Conclusion Based on the recommendations of the WHO in relation to COVID-19, universities need to effectively manage the information they provide to students and build trust through risk communication and community engagement. One important area in this regard is addressing access to mental health services. The reasons why BAME females experience more mental health issues should be explored further.